Prevalence and characterization of seropositive pregnant for SARS-CoV-2 - Guevara-Ríos, Enrique (2020)
Objective: To describe the prevalence and characteristics of seropositive pregnant women for SARS-CoV-2. Material and methods: Quantitative, cross-sectional and descriptive study. Performed in pregnant women screened for SARS-CoV-2 who met selection criteria at hospital admission. Variables of maternal characteristics, pregnancy complications and newborn condition were collected from the respective medical history. Data analysis was performed using descriptive statistics and 95% confidence intervals. Results: 1477 pregnant women admitted to hospitalization were screened, identifying a seroprevalence of anti-SARS-CoV-2 antibodies in 5.28% (95% CI: 4.22% -6.57%). Among the cases of positive seroprevalence, IgM 11.5% (95% CI: 5.7% -21.3%), IgM / IgG 64.1% (95% CI: 5.7% -21.3%), IgG 19% (95% CI: 15.7% and 35.6) were observed %), 91% of seropositive pregnant women were asymptomatic, 40% of seropositive pregnant women presented some type of pregnancy complication, being more frequent premature rupture of membranes (14.1%), abortion (4.1%) and threat of preterm delivery (4.1%) . Of the pregnant women who finished in labor, 69.6% were vaginally, and 11.6% were preterm. There were no maternal deaths or newborn deaths. Conclusion. Pregnant women with hospitalization criteria for delivery care or pregnancy morbidity have a prevalence of positive serology for SARS-CoV-2 of 5.28%; they are mostly asymptomatic. Possible effects of the SARS-CoV-2 virus are not ruled out due to the findings of preterm labor, premature membrane rupture and spontaneous abortion.